A zinc-based hydrogenation catalyst and preparation method thereof

By preparing a zinc-based hydrogenation catalyst containing ZnO, CuO and additives, the problems of easy poisoning and thermal stability of industrial catalysts are solved, and an efficient and stable hydrogenation reaction is achieved.

CN116159564BActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111404208.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-24
Publication Date
2025-04-25
Estimated Expiration
2041-11-24

AI Technical Summary

Technical Problem

In the industry, hydrogenation catalysts, whether they are copper, nickel or precious metal catalysts, have problems of easy poisoning and thermal stability, especially fear of sulfur poisoning, and copper and nickel catalysts are sensitive to carbonyl iron and carbonyl nickel.

Method used

It provides a sulfur-resistant, carbonyl metal-resistant, high-temperature stable zinc-based hydrogenation catalyst, including active component ZnO, additives ZrO2, MgO, etc. and support CuO, and controls the atomic ratio and microscopic particle size of Cu and Zn elements through a specific preparation method.

Benefits of technology

This catalyst has good sulfur resistance, carbonaceous fund resistance and high temperature stability, which significantly improves the activity and selectivity of the hydrogenation reaction.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the field of catalyst technology, and specifically relates to a zinc-based hydrogenation catalyst and a preparation method thereof. The catalyst is composed of an active component, an auxiliary agent and a carrier, wherein the active component is ZnO, the carrier is CuO, and the size of the catalyst microscopic particles is less than 0.1-0.5 nm; the atomic ratio of Cu and Zn elements varies from 0 to n from a point on the boundary of the cross-sectional geometric figure to the center of the microscopic particles, wherein n is 4-15; the preparation process is to add a mixed salt solution containing zinc, copper and an auxiliary agent and a precipitant solution to deionized water in parallel, control the flow rate during the gradual heating process, and keep the pH of the deionized water solution between 7.2 and 7.5; after solid-liquid separation, the filter cake is washed, dried, rapidly roasted, and formed to obtain the catalyst. The catalyst of this patented technology has good sulfur resistance and high temperature stability, and is easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a zinc-based hydrogenation catalyst and a preparation method thereof. Background Art

[0002] Catalytic hydrogenation is an important unit technology for coal deep processing, oil refining, petrochemicals and organic chemicals, including CO hydrogenation, CO2 hydrogenation, benzene ring hydrogenation, aromatic selective hydrogenation, hydrocracking, etc. The application fields and reactions involved are very wide. Hydrogenation catalysts are mainly divided into copper catalysts, precious metal catalysts, nickel catalysts and other system catalysts.

[0003] Chinese patent CN201910853517.8 discloses a catalyst for catalytic hydrogenation of n-butyraldehyde to n-butanol and its preparation method. The catalyst includes an active component Cu, an additive Ni and a catalyst carrier SiO2. The catalyst is prepared by precipitation method, and the specific surface area of ​​the catalyst is 100 m 2 / g~230 m 2 / g, the average pore size is 8.6nm~13nm, and the average pore volume is 0.35ml / g~0.65ml / g. The catalyst of the invention has high n-butyraldehyde conversion rate, high n-butanol selectivity and high stability.

[0004] Chinese patent CN106732620B discloses a nickel-based hydrogenation catalyst and its preparation method. A nickel-containing alumina carrier is impregnated with a nickel-containing solution, and the catalyst is obtained by drying and calcining; the nickel-containing alumina carrier is obtained by molding and calcining nickel-containing pseudo-boehmite; wherein the preparation process of the nickel-containing pseudo-boehmite includes acid-base neutralization and gelation process. The invention organically combines nickel and pseudo-boehmite, so that the active component nickel is effectively dispersed in the pseudo-boehmite, and a nickel-containing alumina carrier of a specific crystal form is formed, and at the same time, the pore structure and acidity of the carrier are well regulated. The catalyst finally obtained has high hydrogenation activity and selectivity, and good chemical stability and thermal stability.

[0005] Chinese patent CN109569686B discloses the preparation of a nitrogen-modified carbon-supported noble metal hydrogenation catalyst and its application in the hydrogenation reaction of halogenated nitrobenzenes. The activated carbon whose surface only contains CO2 leaving groups and the total content of CO2 leaving groups is not higher than 0.8 μmol / g is oxidized with a treatment agent, wherein the treatment agent is oxalic acid or hydrogen peroxide, to obtain pretreated activated carbon; primary amine organic matter is dissolved in water, the pretreated activated carbon is added and mixed thoroughly, and then placed in a hydrothermal kettle for hydrothermal reaction in a CO2 atmosphere to obtain nitrogen-modified activated carbon; precious metal palladium and / or platinum are loaded onto nitrogen-modified activated carbon by ultraviolet light reduction method to obtain a nitrogen-modified carbon-supported noble metal hydrogenation catalyst. The catalyst is applied to the catalytic hydrogenation reduction reaction of halogenated nitrobenzenes, and has the characteristics of high conversion rate, good selectivity, good stability and fast hydrogenation rate.

[0006] Industrial hydrogenation catalysts, whether copper, nickel or precious metal catalysts, are susceptible to poisoning and thermal stability, especially sulfur poisoning. In addition, copper and nickel catalysts are also very sensitive to carbonyl iron and carbonyl nickel. The development of new and efficient hydrogenation catalysts is crucial to upgrading industrial hydrogenation technology, improving energy efficiency and ensuring the safe, long-term and optimal operation of industrial equipment. Summary of the invention

[0007] 1. Technical problems to be solved:

[0008] Industrial hydrogenation catalysts, whether copper, nickel or precious metal catalysts, are susceptible to poisoning and thermal stability, especially sulfur poisoning. In addition, copper and nickel catalysts are also very sensitive to carbonyl iron and carbonyl nickel.

[0009] 2. Technical solution:

[0010] In order to solve the above problems, the present invention provides a sulfur-resistant, carbonyl-resistant, high-temperature stable zinc-based hydrogenation catalyst. A zinc-based hydrogenation catalyst comprises an active component, an additive and a carrier, wherein the active component is ZnO, the carrier is CuO, and the microscopic particle size is less than 0.1-0.5 nm; the atomic ratio of Cu and Zn elements varies from 0 to n from a point on the boundary of the cross-sectional geometric figure to the center of the microscopic particle, wherein n is 4-15.

[0011] The auxiliary agent is at least one of ZrO2, MgO, CaO, CeO2, La2O3, Al2O3, and SiO2.

[0012] The atomic ratio of Zn to Cu is 0.1~10.

[0013] The cation and Zn atomic ratio of the auxiliary agent is 0.05-0.5.

[0014] The present invention also provides a method for preparing the zinc-based hydrogenation catalyst, comprising adding a mixed salt solution containing zinc, copper and an auxiliary agent and a precipitant solution into deionized water in parallel, controlling the flow rate during the gradual heating process to maintain the pH value of the deionized water solution between 7.2 and 7.5; after solid-liquid separation, washing, drying, rapid calcining and molding the filter cake to obtain the catalyst.

[0015] The mixed salt is one of nitrate, chloride and sulfate.

[0016] The precipitant is one of ammonia water, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium hydroxide and potassium hydroxide.

[0017] The gradual heating is performed at a heating rate of 2-10°C / min; and the terminal temperature is less than 80°C.

[0018] The rapid calcination is to adjust the muffle furnace to 300-800° C. and place the catalyst in the muffle furnace for calcination for 1-10 minutes.

[0019] 3. Beneficial effects:

[0020] Compared with the existing copper-based, nickel-based and noble metal hydrogenation catalyst systems, the zinc-based hydrogenation catalyst prepared by the present invention has excellent sulfur resistance, carbonyl group resistance and high temperature stability. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the embodiments.

[0022] Example 1

[0023] 1L mixed salt solution containing 0.1mol zinc nitrate, 1mol copper nitrate, 0.03mol magnesium nitrate and 0.02mol zirconium nitrate and 1mol / L sodium carbonate solution were added to 200mL deionized water in parallel. The temperature of the deionized water system was raised from 25℃ to 65℃ at a rate of 4℃ / min. The flow rate was controlled to keep the pH of the deionized water solution between 7.2 and 7.5. After the precipitation was completed, the filter cake was filtered and washed with deionized water to remove the sodium ions in the filter cake. The filter cake was placed in a forced air drying oven and dried at 100℃ for 4h. Then the muffle furnace was heated to 500℃, and the dried filter cake was placed in the muffle furnace and calcined for 4min and taken out. After cooling to room temperature, the sheet was formed into a φ5×5mm cylinder to obtain ZC1 catalyst. The catalyst was analyzed by spherical aberration corrected electron microscopy (AC-TEM). It was found that the size of the catalyst microscopic particles was 0.1nm. The atomic ratio of Cu and Zn elements varied from 0 to 15 from the boundary point to the center of the microscopic particles along the cross-sectional geometric figure.

[0024] Example 2

[0025] A 1L mixed salt solution containing 0.2mol zinc sulfate, 1mol copper sulfate, 0.04mol cerium nitrate and 0.04mol zirconium nitrate and a 1mol / L sodium bicarbonate solution were added to 200mL deionized water in parallel, and the temperature of the deionized water system was increased from 25°C to 60°C at a rate of 2°C / min. The flow rate was controlled to keep the pH of the deionized water solution between 7.2 and 7.5; after the precipitation was completed, the filter was filtered and the filter cake was washed with deionized water to remove the sodium ions in the filter cake; the filter cake was placed in a forced air drying oven at 100°C and dried for 4h; then the muffle furnace was heated to 600°C, the dried filter cake was placed in the muffle furnace and calcined for 3min and taken out; after cooling to room temperature, it was formed into a φ5×5mm cylinder to obtain a ZC2 catalyst. The catalyst was analyzed using spherical aberration corrected electron microscopy (AC-TEM) and found that the scale of the catalyst microparticles was 0.15nm; the atomic ratio of Cu and Zn elements varied from 0 to 12 from a point on the boundary of the cross-sectional geometric figure to the center of the microparticles.

[0026] Example 3

[0027] A 1L mixed salt solution containing 0.5mol zinc chloride, 1mol copper chloride, 0.02mol lanthanum nitrate and 0.005mol zirconium nitrate was added to 200mL deionized water in parallel with a 0.5mol / L ammonia solution. The temperature of the deionized water system was increased from 25°C to 70°C at a rate of 5°C / min. The flow rate was controlled to keep the pH of the deionized water solution between 7.2 and 7.5. After the precipitation was completed, the filter was filtered and the filter cake was washed with deionized water to remove ammonia in the filter cake. The filter cake was placed in a forced air drying oven and dried at 100°C for 4h. Then the muffle furnace was heated to 700°C, and the dried filter cake was placed in the muffle furnace and roasted for 2min and taken out. After cooling to room temperature, the filter cake was formed into a φ5×5mm cylinder to obtain a ZC3 catalyst. The catalyst was analyzed using spherical aberration corrected electron microscopy (AC-TEM) and found that the scale of the catalyst microparticles was 0.2nm; the atomic ratio of Cu and Zn elements varied from 0 to 10 from a point on the boundary of the cross-sectional geometric figure to the center of the microparticles.

[0028] Example 4

[0029] 1L mixed salt solution containing 1mol zinc nitrate, 1mol copper nitrate, 0.02mol lanthanum nitrate and 0.03mol zirconium nitrate and 1mol / L sodium hydroxide solution were added to 200mL deionized water in parallel. The temperature of the deionized water system was raised from 25℃ to 80℃ at a rate of 10℃ / min. The flow rate was controlled to keep the pH of the deionized water solution between 7.2 and 7.5. After the precipitation was completed, the filter cake was filtered and washed with deionized water to remove the sodium ions in the filter cake. The filter cake was placed in a forced air drying oven and dried at 100℃ for 4h. Then the muffle furnace was heated to 800℃, and the dried filter cake was placed in the muffle furnace and roasted for 1min and taken out. After cooling to room temperature, the sheet was formed into a φ5×5mm cylinder to obtain ZC4 catalyst. The catalyst was analyzed by spherical aberration corrected electron microscopy (AC-TEM). It was found that the size of the catalyst microscopic particles was 0.5nm. The atomic ratio of Cu and Zn elements from the boundary point to the center of the microscopic particles along the cross-sectional geometric figure varied from 0 to 8.

[0030] Example 5

[0031] 1L mixed salt solution containing 1mol zinc nitrate, 0.5mol copper nitrate, 0.01mol calcium nitrate and 0.01mol aluminum nitrate and 1mol / L potassium carbonate solution were added to 200mL deionized water in parallel. The temperature of the deionized water system was raised from 25℃ to 70℃ at a rate of 5℃ / min. The flow rate was controlled to keep the pH of the deionized water solution between 7.2 and 7.5. After the precipitation was completed, the filter cake was filtered and washed with deionized water to remove potassium ions in the filter cake. The filter cake was placed in a forced air drying oven and dried at 100℃ for 4h. Then the muffle furnace was heated to 400℃, and the dried filter cake was placed in the muffle furnace and roasted for 6min and taken out. After cooling to room temperature, the sheet was formed into a φ5×5mm cylinder to obtain ZC5 catalyst. The catalyst was analyzed by spherical aberration corrected electron microscopy (AC-TEM). It was found that the size of the catalyst microscopic particles was 0.2nm. The atomic ratio of Cu and Zn elements from the boundary point to the center of the microscopic particles along the cross-sectional geometric figure varied from 0 to 6.

[0032] Example 6

[0033] 1L mixed salt solution containing 1mol zinc nitrate, 0.3mol copper nitrate, 0.01mol silica sol and 0.02mol aluminum nitrate and 1mol / L potassium hydroxide solution were added to 200mL deionized water in parallel. The temperature of the deionized water system was raised from 25℃ to 70℃ at a rate of 5℃ / min. The flow rate was controlled to keep the pH of the deionized water solution between 7.2 and 7.5. After the precipitation was completed, the filter cake was filtered and washed with deionized water to remove potassium ions in the filter cake. The filter cake was placed in a forced air drying oven and dried at 100℃ for 4h. Then the muffle furnace was heated to 400℃, and the dried filter cake was placed in the muffle furnace and roasted for 6min and taken out. After cooling to room temperature, the sheet was formed into a φ5×5mm cylinder to obtain ZC6 catalyst. The catalyst was analyzed by spherical aberration corrected electron microscopy (AC-TEM). It was found that the size of the catalyst microscopic particles was 0.3nm. The atomic ratio of Cu and Zn elements changed from 0 to 5 from the boundary point to the center of the microscopic particle along the cross-sectional geometric figure.

[0034] Example 7

[0035] A 1L mixed salt solution containing 1mol zinc nitrate, 0.1mol copper nitrate, 0.01mol silica sol and 0.02mol aluminum nitrate was added to 200mL deionized water in parallel with a 1mol / L potassium bicarbonate solution. The temperature of the deionized water system was increased from 25°C to 70°C at a rate of 4°C / min. The flow rate was controlled to keep the pH of the deionized water solution between 7.2 and 7.5. After the precipitation was completed, the filter was filtered and the filter cake was washed with deionized water to remove potassium ions in the filter cake. The filter cake was placed in a forced air drying oven and dried at 100°C for 4h. Then the muffle furnace was heated to 300°C, and the dried filter cake was placed in the muffle furnace and roasted for 10min and taken out. After cooling to room temperature, the filter cake was formed into a φ5×5mm cylinder to obtain a ZC7 catalyst. The catalyst was analyzed using spherical aberration corrected electron microscopy (AC-TEM) and found that the scale of the catalyst microparticles was 0.5nm; the atomic ratio of Cu and Zn elements varied from 0 to 4 from a point on the boundary of the cross-sectional geometric figure to the center of the microparticles.

[0036] Example 8

[0037] The catalyst prepared in Example 1-7 was used for CO2 hydrogenation to produce methanol: 50 mL of the catalyst was loaded into the constant temperature section of a fixed bed reactor (inner diameter: 35 mm), and a H2-N2 mixed gas containing 5% H2 was used at 230°C, normal pressure, and a space velocity of 2000 h -1 The condition was restored for 10 h, and then switched to an airspeed of 10000 h -1The raw gas (containing 72% H2, 24% CO2, 4% N2, H2S content of 10ppm, Fe(CO)5 content of 5ppm), the pressure was raised to 5MPa, after 2h of reaction, the tail gas composition was analyzed by gas chromatography, and the CO2 conversion rate and methanol selectivity were calculated as the initial activity. The heat-resistant conditions were normal pressure, 400℃, 5h, and then restored to the initial activity test reaction conditions. The CO2 conversion rate and methanol selectivity obtained after stabilization for 2h were the post-heat-resistant activity. For comparison, industrial methanol synthesis catalyst C307 was selected as a comparison, and the results are shown in Table 1.

[0038] Example 9

[0039] The catalyst prepared in Example 1-7 was used for hydrogenation of isononanal to produce isononanol: 100 mL of the catalyst was loaded into the constant temperature section of a fixed bed reactor (inner diameter: 35 mm), and a H2-N2 mixed gas containing 5% H2 was used at 230°C, normal pressure, and a space velocity of 2000 h -1 The reduction was carried out under the same conditions for 10 h, and then switched to isononanal. The feed volume space velocity of isononanal (purity of 98.5%, heavy component content of 0.02 wt%) was 0.5 h -1 , reaction pressure is 3MPa, reaction temperature is 160℃, reaction hydrogen / aldehyde ratio is 8, 10ppm H2S is added to hydrogen, sampling and analysis begins after the reaction operation is stable for 10h, one sample is taken every 1h, and the average value of 10 times is taken as the final result. For comparison, the industrial isononanal hydrogenation to isononanol catalyst Y is used for comparison, and the results are shown in Table 2.

[0040] Table 1 Catalyst performance in CO2 hydrogenation to methanol reaction

[0041] .

[0042] As can be seen from Table 1, the catalyst prepared by the patented technology of the present invention, compared with the industrial methanol synthesis catalyst, has higher activity, methanol selectivity and high temperature stability in the CO2 hydrogenation to methanol reaction when there are 10ppm H2S and 5ppmFe(CO)5 in the feed gas.

[0043] Table 2 Comparison with industrial isononanal hydrogenation catalyst to isononanol

[0044] .

[0045] As can be seen from Table 2, the catalyst prepared by the patented technology of the present invention has higher activity and isononanol selectivity when there is 10 ppm H2S in hydrogen, compared with the industrial isononanal hydrogenation catalyst to isononanol.

Claims

1. Application of a zinc-based hydrogenation catalyst in hydrogenating isononanal to isononanol, characterized in that: The catalyst comprises an active component, an auxiliary agent and a carrier, wherein the active component is ZnO, the carrier is CuO, and the size of the microscopic particles is 0.1-0.5 nm; the atomic ratio of Cu and Zn elements varies from 0 to n from a point on the boundary of the cross-sectional geometric figure to the center of the microscopic particles, wherein n is 4-15; the preparation method of the catalyst comprises the following steps: adding a mixed salt solution containing zinc, copper and an auxiliary agent and a precipitant solution to deionized water in parallel, controlling the flow rate during the gradual heating process, and maintaining the pH value of the deionized water solution between 7.2 and 7.5; after solid-liquid separation, the filter cake is washed, dried, rapidly calcined and formed to obtain a catalyst; the gradual heating is a heating rate of 2-10°C / min, the terminal temperature is less than 80°C, the auxiliary agent is at least one of ZrO2, MgO, CaO, CeO2, La2O3, Al2O3, SiO2, the Zn / Cu atomic ratio is 0.1-10, and the rapid calcination is to adjust the muffle furnace to 300-800°C, and place the catalyst in the muffle furnace and roast for 1-10 minutes.

2. The use according to claim 1, characterized in that: The ratio of the auxiliary agent cation to Zn atoms is 0.05-0.

5.

3. The use according to claim 1, characterized in that: The mixed salt is one of nitrate, chloride and sulfate.

4. The use according to claim 1, characterized in that: The precipitant is one of ammonia water, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium hydroxide and potassium hydroxide.

Citation Information

Patent Citations

  • A nickel-based hydrogenation catalyst and its preparation method

    CN106732620B

  • Preparation of nitrogen-modified carbon-supported noble metal hydrogenation catalysts and their application in the hydrogenation reaction of halonitrobenzenes

    CN109569686B

  • Catalyst for preparing n-butyl alcohol through catalytic hydrogenation of n-butyraldehyde and preparation method of catalyst

    CN112547068A

  • Addition agent modified copper-based catalyst and preparation method and application thereof

    CN109126808A